CONSUMPTIVE BEHAVIOR AMONG ADOLESCENTS IN THE ABDULLAH DAENG SIRUA AREA, MAKASSAR CITY - Muh. Nur Awal; Emanuel Omedetho Jermias; Abdul Rahman (Jurnal Scientia, 2023)
This study aims to determine the form of adolescent consumptive behavior in the Abdullah Daeng Sirua area, Makassar City. This type of research is a qualitative descriptive research. The criteria for teenagers who have a consumptive lifestyle are characterized by hanging out at cafes at least once every 3 months, owning more than one cell phone, going to a beauty salon at least once a month, owning more than 12 pairs of clothes. Data collection techniques using observation and interviews. Data analysis techniques are in the form of descriptive and functional analysis by going through the stages of data collection, data reduction, data presentation and drawing conclusions. While the data validation technique used is member check. The results of the study show that the form of adolescent consumptive behavior is buying products on the basis of maintaining self-appearance and prestige, maintaining status symbols, maintaining high self-confidence, and on consideration of prices being discounted.